Components of the transforming growth factor-β family and the pathogenesis of human Achilles tendon pathology—a genetic association study - Posthumus, Michael; Collins, Malcolm; Cook, Jill; Handley, Christopher J.; Ribbans, William J.; Smith, Roger K. W.; Schwellnus, Martin P.; Raleigh, Stuart M. (Rheumatology (Oxford, England), 2010)
Objectives. Achilles tendon pathology is a multifactorial condition for which various risk factors, including genetic factors, have been identified. Gene transfection of two members of the TGF-β family, TGF-β1 and growth/differentiation factor-5 (GDF-5), have been shown to enhance tendon repair and mechanical strength within animal Achilles tendon injury models. The objective of this study was to investigate whether two functional 5′ untranslated region (UTR) single nucleotide polymorphisms (SNPs), the TGFB1 rs1800469 variant and the GDF5 rs143383 variant, were associated with ATP within an Australian (‘AUS’) and a South African (‘SA’) case–control cohort. Methods. One hundred and seventy-one subjects (58 AUS and 112 SA) with Achilles tendon pathology (ATP group) and 235 (142 AUS and 96 SA) asymptomatic control (CON group) subjects were genotyped for the selected SNPs using custom-designed Taqman assays. A χ2-analysis or Fisher’s exact test was used to analyse any differences in the genotype and allele frequencies. Significance was accepted when P < 0.05. Results. There were no significant TGFB1 rs1800469 genotype (P = 0.491) or allele (P = 0.400) frequency differences between the ATP and CON groups. The TT genotype of the GDF5 rs143383 variant was significantly over-represented in the ATP group of the AUS cohort [P = 0.011; odds ratio (OR) = 2.24; 95% CI 1.21, 4.16], and when the AUS and SA cohorts were combined (P = 0.004; OR = 1.82; 95% CI 1.23, 2.74). Conclusions. In conclusion, this study suggests that individuals with a TT genotype of the functional GDF5 rs143383 variant have twice the risk of developing ATP. This finding highlights a role of GDF-5 in the pathogenesis of Achilles tendon pathology.